2023
DOI: 10.30939/ijastech..1378268
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Automotive Paint Wastewater: Photocatalytic degradation of methylene blue using semi-conductive ZrO2

Mustafa SEYREK,
Filiz BORAN,
Merve OKUTAN

Abstract: Addressing water pollution, particularly in the automotive industry's painting processes, is vital due to its significant environmental impact, and the use of photocatalysis, an environmentally friendly and energy-efficient advanced oxidation method, holds promise for removing non-biodegradable organic dyes from wastewater. In this study, the use of semiconductor ZrO2 nanoparticles in the photocatalytic degradation of pollutants in wastewater under UV light was investigated. Zeta potential, Brunauer–Emmett–Tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Based on the photocatalytic experimental technique carried out under similar conditions, it has been reported that the ZrO 2 nanoparticle generated by optimizing the synthesis conditions has high photocatalytic performance compared with various ZrO 2 nanostructures in the literature. Seyrek et al reported important research on the degradation of methylene blue, and that it is very important to consider changes in the thickness of thin films, annealing temperature, pH, concentrations, and wavelengths of the ultraviolet lamp [88].…”
Section: Photocatalytic Decolorization Of Mbmentioning
confidence: 99%
“…Based on the photocatalytic experimental technique carried out under similar conditions, it has been reported that the ZrO 2 nanoparticle generated by optimizing the synthesis conditions has high photocatalytic performance compared with various ZrO 2 nanostructures in the literature. Seyrek et al reported important research on the degradation of methylene blue, and that it is very important to consider changes in the thickness of thin films, annealing temperature, pH, concentrations, and wavelengths of the ultraviolet lamp [88].…”
Section: Photocatalytic Decolorization Of Mbmentioning
confidence: 99%
“…Synthetic dyes, especially methylene blue (MB), pose a formidable challenge to environmental sustainability, significantly contributing to water pollution [1]. With the capacity to be detected in water at minimal concentrations (as low as one mg/L) and commonly found in textile effluents at levels ranging from 10 to 200 mg/L [2], the prevalence of MB across diverse industrial applications, including textiles, printing, and cosmetics, has led to its widespread dissemination into aquatic environments [3,4].…”
Section: Introductionmentioning
confidence: 99%